La informática educativa y su incidencia en el desarrollo del pensamiento crítico de los estudiantes de la Unidad Educativa “Carlos Alberto Aguirre Avilés” de la Parroquia La Unión, del cantón Babahoyo - Castro Vera, Isaías Ramón (2019)
This research work was developed in the educational institution "Carlos Alberto Aguirre Avilés" and is specifically oriented to the issue of educational informatics and its impact on the development of critical thinking of the students of the third year of the Unified General Baccalaureate. The main problem was to determine if educational informatics have a positive impact on the development of the critical thinking of the students of the unified general baccalaureate of the Educational Unit “Carlos Alberto Aguirre Avilés” of the parish La Unión, of the Babahoyo canton, for which it was carried out the elaboration of the analysis that demonstrates the truth or falsity of the fact. It was seen in this research the need to implement, tools of educational informatics, so that this, help to obtain a better development of the critical thinking of the students and in turn to share a large amount of certified information, in addition to providing the facility of learn effectively and easily through the options offered, which if used with the manual, will contribute to the academic reinforcement of the students of the third year of unified general baccalaureate of the Educational Unit "Carlos Alberto Aguirre Avilés", achieving In this way, generate the interest on the part of teachers and students to use the resources of educational informatics that will allow them to improve the quality of their thinking and can integrate it into the academic activities of the educational institution